2022
DOI: 10.1021/acscentsci.1c01381
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production of Reduced Phosphorus Compounds: Mechanochemical Hydride Phosphorylation Using Condensed Phosphates as a Route to Phosphite

Abstract: In pursuit of a more sustainable production of phosphorous acid (H 3 PO 3 ), a versatile chemical with phosphorus in the +3 oxidation state, we herein report that condensed phosphates can be employed to phosphorylate hydride reagents under solvent-free mechanochemical conditions to furnish phosphite (HPO 3 2– ). Using potassium hydride as the hydride source, sodium trimetaphosphate (Na 3 P 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 83 publications
(128 reference statements)
0
17
0
Order By: Relevance
“…In recent years, the chemical researchers demonstrated that he important organic chemical structures such as CO [8], CH 4 [9], HCOOH [10], HCHO [11] and CH 3 OH [12] are possible products of processes of CO 2 reduction reaction [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the chemical researchers demonstrated that he important organic chemical structures such as CO [8], CH 4 [9], HCOOH [10], HCHO [11] and CH 3 OH [12] are possible products of processes of CO 2 reduction reaction [13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the chemical researchers demonstrated that he important organic chemical structures such as CO [8], CH 4 [9], HCOOH [10], HCHO [11] and CH 3 OH [12] are possible products of processes of CO 2 reduction reaction [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of ACS Central Science , Cummins and co-workers report a facile and selective reduction of polyphosphates to phosphite with potassium hydride via mechanosynthesis, a potential solution toward a “greener” phosphorus industry. 1 Phosphorus generally exists in its highest oxidation state in nature and is a vital element for living organisms. It constitutes approximately 1% of the human body weight as a component of bone, membrane, nucleic acids, and high-energy phosphates.…”
mentioning
confidence: 99%
“…To synthesize P(III) chemicals from phosphates with reagents that are easy to handle, Cummins and co-workers now report the reduction of polyphosphates with potassium hydride under solvent-free conditions. 1 Grinding the polyphosphate/hydride mixture in a ball mill is the key to achieving a high yield of phosphite. The friction and impact generated during milling promote the reaction between solid polyphosphates and potassium hydride at room temperature that produces phosphite with good selectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation